Why School Adolescent Girls Elope? Perspective from School Teachers - Ghimire, Sudha (Journal of Health Promotion, 2018)
Marriage is considered as compulsive ritual by all societies, though it has been explained differently by different cultural groups. In Nepal the prevalence of love marriage varies between communities, regions, castes and ethnic groups, but most of the time they are early before the legal age of marriage. In this context, this paper explores the views from school officials regarding the reasons of early marriage, where they have highlighted the cultural practices, social media, lack of transformative sexuality education from schools, gap in the contents of school curriculum regarding sexual and reproductive health. For the purpose of data collection teachers from Baira Mahdev School were purposively selected and in-depth interviews were conducted for exploring their views. The collected data were analyzed on thematic basis and relevant themes were generated.Journal of Health Promotion Vol.6 2008, p.80-85